Edukasi Kesehatan Pengaruh Kualitas Tidur Terhadap Kadar Hb dan Imunitas Tubuh Pada Remaja - Anas Fadli Wijaya; Rian Anggia Destiawan; Pratikah Verdianti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2021)
Sleep quality is a state lived by an individual to produce freshness and fitness after waking up. If a person's sleep quality is poor it will cause a decrease in the body's immune system and Hb levels which causes the individual to feel easily tired, sleepy and susceptible to disease. Adolescents are identified as a population at high risk of experiencing sleep problems which disrupt sleep quality. Accumulated work and lifestyle are one of the factors causing poor sleep patterns in adolescents which makes it easier for them to experience sleep disturbances. Adolescents with high risk certainly need adequate knowledge regarding the importance of maintaining quality sleep related to the body's immune system and Hb levels. Increased knowledge and examination can be carried out by laboratory personnel with health counseling and laboratory tests. The purpose of this community service is to increase the knowledge of adolescents to maintain good quality sleep so that Hb levels and body immunity are maintained. This community service implementation method consists of three stages, namely the preparation, implementation, and evaluation stages. At the implementation stage, an examination of Hb levels and counting the number of types of leukocytes was carried out as well as education related to the effect of sleep quality on Hb levels and the body's immune system. As a result of community service, adolescents have obtained health status through laboratory tests and good knowledge about the effect of sleep quality on Hb levels and body immunity.